Attractor bifurcation for FKPP type equation with periodic boundary condition

Boundary Value Problems20122012:41

DOI: 10.1186/1687-2770-2012-41

Received: 31 December 2011

Accepted: 13 April 2012

Published: 13 April 2012

Abstract

In this article, we make bifurcation analysis on the FKPP type equation under periodic boundary condition. And we show that the solutions bifurcate from the trivial solution u = 0 to an attractor ∑ λ as parameter crosses certain critical value. Moreover, we prove that the attractor ∑ λ consists of only one cycle of steady state solutions and is homeomorphic to S1. The analysis is based on a new theory of bifurcation, called attractor bifurcation, which was developed by Ma and Wang.

2000 Mathematics Subject Classification: 35B; 35Q; 37G; 37L.

Keywords

FKPP type equation periodic boundary condition attractor bifurcation center manifold

1 Introduction

We consider the following reaction diffusion equation of FKPP type:
u t = a u x x + λ u + b u 2 - d u 3 , ( x , t ) R × ( 0 , ) , u ( x , t ) = u ( x + 2 k π , t ) , k Z , ( x , t ) R × ( 0 , ) , u ( x , 0 ) = φ ( x ) , x R , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ1_HTML.gif
(1.1)
supplemented with the following natural constraint:
0 2 π u ( x ) d x = 0 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ2_HTML.gif
(1.2)

where a > 0, d > 0, b are given and λ > 0 is system parameter.

In 1937, the FKPP equation was first proposed by Fisher as a model to describe the propagation of advantageous genes [1] and was studied mathematically by Kolmogorov et al. [2]. Moreover, it was also used as biological models for population dynamics [35].

The FKPP equation has been extensively studied during the last decades. Among all the topics of these, the existence of traveling waves (exact form of solutions) and the asymptotic behavior of solutions attract much attention. Many different kinds of methods for the existence of traveling waves (exact form of solutions) haven been developed, such as Painleve expansion method [6, 7], bilinear method [8, 9], symmetry methods [10]. On the other hand, many results on the asymptotic behavior of solutions are also obtained; see among others [1114] and references therein.

However, there is few work on the attractor bifurcation of the FKPP equation. As a new notion of bifurcation, attractor bifurcation was developed by Ma and Wang [1517] and attracted researchers [18, 19]. Ma and Wang [15] first proposed this new notion and applied it to Rayleigh-Be nard Convection. Afterwards, with this new theory, Park [18] analyzed the bifurcation of the complex Ginzburg-Landau equation (CGLE) and Zhang et al. [19] studied the attractor bifurcation of the Kuramoto-Sivashinsky equation.

In this article, we focus on the attractor bifurcation of FKPP type Equation (1.1). The bifurcation analysis near the first eigenvalue of (1.1) will be discussed. The topology structure of the bifurcated solutions will also be studied. As a result, we show the system bifurcates from the trivial solution to an attractor ∑ λ as system parameter λ crosses the critical value a, the first eigenvalue of the eigenvalue problem of the linearized equation of (1.1). Furthermore, we prove that ∑ λ is homeomorphic to S1 and consists of only one cycle of steady state solutions.

This article is organized as follows. The mathematical setting are given in Section 2. The main results are stated in Section 3. The preliminaries are put in section 4. And Section 5 devote to the proof of the main theorem.

2 Mathematical setting

Let
H = L 2 ( 0 , 2 π ) , H 1 = u H 2 ( 0 , 2 π ) 0 2 π u ( x ) d x = 0 , u ( x + 2 k π ) = u ( x ) , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equa_HTML.gif
and we define L λ = -A + B λ : H1H and G : H1H by
A u = - a u x x , B λ u = λ u , G u = b u 2 - d u 3 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equb_HTML.gif
Consequently, we have an operator equation which is equivalent to the problem (1.1):
d u d t = L λ u + G ( u ) , u ( x , 0 ) = φ . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ3_HTML.gif
(2.1)
Thanks to the existence result of semi-linear evolution equations, see Temam [20], Pazy [21], we can define a semigroup
S ( t ) : H 1 H , t 0 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equc_HTML.gif

which satisfies the semigroup property.

3 Main results

3.1 The definition of attractor bifurcation

In order to state the main theorem of this article, we start with the definition of attractor bifurcation which was first proposed by Ma and Wang in [1517].

Let H and H1 be two Hilbert spaces, and H1H be a dense and compact inclusion. We consider the following nonlinear evolution equations
d u d t = L λ u + G ( u ) , u ( x , 0 ) = u 0 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ4_HTML.gif
(3.1)
where u : [0, ∞) → H is the unknown function, λR is the system parameter, and L λ :H1: → H are parameterized linear completely continuous fields depending continuously on λ, which satisfy
L λ = - A + B λ a sectorial operator, A : H 1 H a linear homeomorphism, B λ : H 1 H a parameterized linear compact operators . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ5_HTML.gif
(3.2)
Since L λ is a sectorial operator which generates an analytic semigroup S λ ( t ) = { e t L λ } t 0 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq1_HTML.gif for any λR, we can define fractional power operators (-L λ ) μ for 0 ≤ μ ≤ 1 with domain H μ = D((-L λ ) μ ) such that H μ 1 H μ 2 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq2_HTML.gif if μ1 > μ2, and H0 = H. In addition, we assume that the nonlinear terms G(., λ) : H α H for some 0 ≤ α < 1 are a family of parameterized C r bounded operator (r ≥ 1) continuously depending on λ, such that
G ( u , λ ) = o u H α , λ R . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ6_HTML.gif
(3.3)
Definition 3.1.1 A set Σ ⊂ H is called an invariant set of (3.1) if S(t) Σ = Σ for any t ≥ 0. An invariant set Σ ⊂ H of (3.1) is said to be an attractor if Σ is compact, and there exists a neighborhood of WH of Σ such that for any ψ0W we have
lim t dis t H ( ψ ( t , ψ 0 ) , Σ ) = 0 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equd_HTML.gif
Definition 3.1.2 (1) We say that the solution to Equation (3.1) bifurcates from (ψ, λ) = (0, λ0) to an invariant set Ω λ , if there exists a sequence of invariant sets { Ω λ n } http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq3_HTML.gif of (3.1) such that 0 Ω λ n http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq4_HTML.gif, and
lim n λ n = λ 0 , lim n max x Ω λ n x = 0 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Eque_HTML.gif
  1. (2)

    If the invariant sets Ω λ are attractors of (3.1), then the bifurcation is called attractor bifurcation.

     

3.2 Main theorem

In this article, based on attractor bifurcation theory we obtain the following results.

Theorem 3.2.1 For the problem (1.1) with (1.2), if 2b2 < 9ad, following assertions hold true:
  1. (1)

    if λa, the steady state u = 0 is locally asymptotically stable. Furthermore, if b = 0, the steady state u = 0 is globally asymptotically stable.

     
  2. (2)

    if λ > a, the Equation (1.1) bifurcates from u = 0 to an attractor Σ λ which is homeomorphic to S 1.

     
  3. (3)

    Σ λ consists of exactly one cycle of steady solutions of (1.1).

     
  4. (4)

    There exists a neighborhood U of u = 0, such that Σ λ attracts U/Γ, where Γ is the stable manifold of u = 0 with co-dimension 2 in H.

     

4 Preliminaries

4.1 Attractor bifurcation theory

In the following, we proceed with the principle of exchange of stabilities (PES). Let the eigenvalues (counting multiplicity) of L λ be given by
β k ( λ ) C ( k 1 ) . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equf_HTML.gif
Suppose that
β i ( λ ) < 0 , i f λ < λ 0 = 0 , i f λ = λ 0 ( 1 i m ) > 0 , i f λ < λ 0 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ7_HTML.gif
(4.1)
β j ( λ 0 ) < 0 , j m + 1 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ8_HTML.gif
(4.2)
Let the eigenspace of L λ at λ = λ0 be
E 0 = 1 j m k = 1 { u , v H 1 ( L λ 0 - β j ( λ 0 ) ) k w = 0 , w = u + i v } . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equg_HTML.gif

It is known that dim E0 = m.

Theorem 4.1.1[17] Assume that the conditions (3.2), (3.3), (4.1), and (4.2) hold true, and u = 0 is locally asymptotically stable for (3.1) at λ = λ0. Then the following assertions hold true:
  1. (1)

    (3.1) bifurcates from (u, λ) = (0, λ 0) to attractors Ω λ , having the same homology as S m -1, for λ > λ 0, with m - 1 ≤ dim Ω λ m, which is connected as m > 1;

     
  2. (2)
    for any u λ ∈ Ω λ , u λ can be expressed as
    u λ = v λ + o v λ H 1 , v λ E 0 ; http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equh_HTML.gif
     
  3. (3)

    There is an open set UH with 0 ∈ U such that the attractor Ω λ bifurcated from (0, λ 0) attracts U/Γ in H, where Γ is the stable manifold of u = 0 with co-dimension m.

     

To get the structure of the bifurcated solutions, we introduce another theorem.

Let v be a two-dimensional C r (r ≥ 1) vector field given by
v λ ( x ) = λ x - F ( x , λ ) , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ9_HTML.gif
(4.3)
for xR2. Here
F ( x , λ ) = F k ( x , λ ) + o ( x k ) , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ10_HTML.gif
(4.4)
where F k is a k-multilinear field, which satisfies an inequality
C 1 x k + 1 < F k ( x , λ ) , x > C 2 x k + 1 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ11_HTML.gif
(4.5)

for some constants 0 < C1 < C2 and k = 2m + 1, m ≥ 1.

Theorem 4.1.2 ([[16], Theorem 5.10, p. 134]) Under conditions (4.4) and (4.5), the vector field (4.3) bifurcates from (x, λ) = (0, 0) to an attractor Π λ for λ > 0, which is homeomorphic to S1. Moreover, one and only one of the following is true.
  1. (1)

    Π λ is a period orbit,

     
  2. (2)

    Π λ consists of infinitely many singular points,

     
  3. (3)

    Π λ contains at most 2(k + 1) = 4(m + 1) singular points, and has 4N + n (N + n ≥ 1) singular points, 2N of which are saddle points, 2N of which are stable node points (possibly degenerate), and n of which have index zero.

     

4.2 Center manifold reduction

Since the key point in the proof of Theorem 3.2.1 is the center manifold function, we introduce an approximation formula of the center manifold function derived in [16].

We assume that the spaces H1 and H can be decomposed into
H 1 = E 1 λ E 2 λ , dim E 1 λ < , near λ 0 R , H = 1 λ 2 λ , 1 λ = E 1 λ , 2 λ = the closure of E 2 λ in H , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ12_HTML.gif
(4.6)
where E 1 λ , E 2 λ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq5_HTML.gif are invariant spaces of L λ , i.e., L λ can be decomposed into L λ = L 1 λ L 2 λ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq6_HTML.gif such that for any λ near λ0,
L 1 λ = L λ | E 1 : E 1 λ 1 λ , L 2 λ = L λ | E 2 : E 2 λ 2 λ , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ13_HTML.gif
(4.7)

where all eigenvalues of L 2 λ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq7_HTML.gif possess negative real parts, all eigenvalues of L 1 λ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq8_HTML.gif possess nonnegative real parts at λ = λ0.

Thus, for λ near λ0, (3.1) can be rewritten as
d x d t = L 1 λ + G 1 ( x + y , λ ) , d y d t = L 2 λ + G 2 ( x + y , λ ) , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equi_HTML.gif
where u = x + y H 1 , x E 1 λ , y E 2 λ , G i = P i G ( u , λ ) http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq9_HTML.gif, and P i : H i http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq10_HTML.gif are canonical projections. Moreover, let
E 2 λ ( α ) = closure of E 2 λ in H α , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equj_HTML.gif

where α < 1 given by (3.3).

By the classical center manifold theorem (see among others [20, 22]), there exists a neighborhood of λ0, a neighborhood B λ E 1 λ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq11_HTML.gif of x = 0, and a C1 center manifold function Φ ( . , λ ) : B λ E 2 λ ( α ) http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq12_HTML.gif, depending continuously on λ. Then to investigate the dynamic bifurcation of (3.1) it suffices to consider the finite dimensional system as follows
d x d t = L 1 λ + G 1 ( x + Φ λ ( x ) , λ ) , x B λ E 1 λ . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equk_HTML.gif
Assume the nonlinear operator G be in the following form
G ( u , λ ) = G k ( u , λ ) + o ( u k ) , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ14_HTML.gif
(4.8)
for some integer k ≥ 2. Here G k is a k-multilinear operator
G k : H 1 × × H 1 H , G k ( u , λ ) = G k ( u , , u , λ ) . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equl_HTML.gif
Theorem 4.2.1 ([[16], Theorem 3.8, p. 63]) Under the conditions (3.2), (4.1), (4.2), (4.6), and (4.8), the center manifold function Φ(x, λ) can be expressed as
Φ ( x , λ ) = ( - L 2 λ ) - 1 P 2 G k ( x , λ ) + O β x k + o x k , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ15_HTML.gif
(4.9)

where L 2 λ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq7_HTML.gif is as in (4.7), P 2 : H 2 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq13_HTML.gif the canonical projection, x E 1 λ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq14_HTML.gif, and β = β 1 λ , , β m λ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq15_HTML.gif the eigenvalues of L 1 λ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq8_HTML.gif.

5 Proof of main theorem

In this section, we shall prove Theorem 3.2.1 by four steps.

Step 1. In this step, we shall study the eigenvalue problem of the linearized equation of (2.1) and shall find the eigenvectors and the critical value of λ.

Consider the eigenvalue problem of the linear equation,
L λ u = β u . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ16_HTML.gif
(5.1)
Note that the eigenvalues { ρ k } k = 1 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq16_HTML.gif and eigenvectors { e k } k = 1 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq17_HTML.gif of Laplace operator, which satisfy
d 2 d x 2 e k = ρ k e k , e k ( x + 2 k π ) = e k ( x ) , 0 2 π e k ( x ) d x = 0 , 0 2 π e k 2 ( x ) d x = 1 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equm_HTML.gif
are
ρ k = - k 2 , e k = sin kx π o r cos kx π . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equn_HTML.gif
Then the eigenvalues and eigenvectors of (5.1) are
β 2 k - 1 = β 2 k = λ - a k 2 , e 2 k - 1 = sin kx π , e 2 k = cos kx π . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ17_HTML.gif
(5.2)
Now, we get the PES:
β 1 ( λ ) = β 2 ( λ ) < 0 , λ < a , = 0 , λ = a , > 0 , λ > a , β j ( a ) < 0 , j 3 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equo_HTML.gif

As a result, conditions (4.1) and (4.2) are verified.

Step 2. We verify that for any λR, operator L λ + G satisfies conditions (3.2) and (3.3).

From the theory of elliptic equations, operator A : H1H is a homeomorphism. Note that conclusion H1H is compact, then operator B λ : H1H is linear compact operator. Thanks to the results of analytic semigroup in [2022], from (5.2) we know that operator L λ : H1H is a sectorial operator which generates an analytical semigroup. Condition (3.2) is verified.

It is easy to get the following inequality
G ( u ) H 2 = 0 2 π b u 2 - d u 3 2 d x C 0 2 π ( u 4 + u 6 ) d x C u L 4 ( 0 , 2 π ) 4 + u L 6 ( 0 , 2 π ) 6 C u H 1 2 4 + u H 1 2 6 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equp_HTML.gif
which implies that G ( u ) = o u H 1 2 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq18_HTML.gif, where
H 1 2 = u H 1 ( 0 , 2 π ) 0 2 π u ( x ) d x = 0 , u ( x + 2 k π ) = u ( x ) , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equq_HTML.gif

condition (3.3) is verified.

Step 3. In this part, we shall prove the existence of attractor bifurcation and analyze the topological structure of attractor Σ λ .

Let E 1 λ = E 0 = span { e 1 , e 2 } , E 2 λ = E 0 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq19_HTML.gif. Let Φ be the center manifold function, in the neighborhood of (u, λ) = (0, a), we have
u = y + Φ ( y ) , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equr_HTML.gif

where y = x1e1 + x2e2.

Then the reduction equations of (2.1) are as follows
d x 1 d t = ( λ - a ) x 1 + < G ( u ) , e 1 > , d x 2 d t = ( λ - a ) x 2 + < G ( u ) , e 2 > . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ18_HTML.gif
(5.3)

To get the exact form of the reduction equations, we need to obtain the expression of < G(u), e1 > and < G(u), e2 >.

Let G2 : H1 × H1H and G3 : H1 × H1 × H1H are the bilinear and trilinear operators of G, respectively, i.e.,
G 2 ( u 1 , u 2 ) = b u 1 u 2 , G 3 ( u 1 , u 2 , u 3 ) = - d u 1 u 2 u 3 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equs_HTML.gif
Since
< G 2 ( x 1 e 1 + x 2 e 2 , x 1 e 1 + x 2 e 2 ) , e 1 > = < G 2 ( x 1 e 1 + x 2 e 2 , x 1 e 1 + x 2 e 2 ) , e 2 > = 0 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equt_HTML.gif

the first-order approximation of (5.3) doesn't work. Now, we shall find out the second-order approximation of (5.3). And the most important of all is to obtain the approximation expression of the center manifold function.

Since
< G 2 ( x 1 e 1 + x 2 e 2 , x 1 e 1 + x 2 e 2 ) , e k > = b x 1 2 0 2 π e 1 2 e k d x + b x 2 2 0 2 π e 2 2 e k d x + 2 b x 1 x 2 0 2 π e 1 e 2 e k d x , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equu_HTML.gif
and
0 2 π e 1 2 e k d x = 0 , k 4 , 0 2 π e 1 2 e 4 d x = - 1 2 π , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ19_HTML.gif
(5.4)
0 2 π e 2 2 e k d x = 0 , k 4 , 0 2 π e 2 2 e 4 d x = 1 2 π , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ20_HTML.gif
(5.5)
0 2 π e 1 e 2 e k d x = 0 , k 3 , 0 2 π e 1 e 2 e 3 d x = 1 2 π , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ21_HTML.gif
(5.6)
we can obtain
< G 2 ( x 1 e 1 + x 2 e 2 , x 1 e 1 + x 2 e 2 ) , e k > = b π x 1 x 2 , k = 3 , b 2 π x 2 2 - b 2 π x 1 2 , k = 4 , 0 , k 3 , 4 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ22_HTML.gif
(5.7)
By the formula (4.9) in Theorem 4.2.1 and (5.7), the center manifold function Φ, in the neighborhood of (u, λ) = (0, a), can be expressed as
Φ ( y ) = - k = 3 β k - 1 < G 2 ( y , y ) , e k > e k + O β 1 2 + β 2 2 y 2 + o y 2 = - ( λ - 4 a ) - 1 b 2 π ( 2 x 1 x 2 e 3 - x 2 2 e 4 + x 1 2 e 4 ) + O λ - a 2 x 1 2 + x 2 2 + o x 1 2 + x 2 2 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equv_HTML.gif
In the following, we calculate < G(u), e j >, j = 1, 2.
< G ( u ) , e j > = < G 2 ( y + Φ ( y ) , y + Φ ( y ) ) , e j > + < G 3 ( y + Φ ( y ) , y + Φ ( y ) , y + Φ ( y ) ) , e j > = < G 2 ( y , Φ ( y ) ) , e j > + < G 2 ( Φ ( y ) , y ) , e j > + G 3 ( y , y , y ) , e j > + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 , j = 1 , 2 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equw_HTML.gif

Next we only need to find out < G2(y, Φ(y)), e j >, < G2(Φ(y),y), e j > and G3(y, y, y), e j >.

By calculation, we have
< G 2 ( y , Φ ( y ) ) , e 1 > = < G 2 ( Φ ( y ) , y ) , e 1 > = 0 2 π b y Φ ( y ) e 1 d x = - ( λ - 4 a ) - 1 b 2 2 π 0 2 π ( x 1 e 1 2 + x 2 e 1 e 2 ) ( 2 x 1 x 2 e 3 - x 2 2 e 4 + x 1 2 e 4 ) d x + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 = - ( λ - 4 a ) - 1 b 2 2 π 0 2 π ( - x 1 3 e 1 2 e 4 + x 1 x 2 2 e 1 2 e 4 + 2 x 1 x 2 2 e 1 e 2 e 3 ) d x + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 , < G 2 ( y , Φ ( y ) ) , e 2 > = < G 2 ( Φ ( y ) , y ) , e 2 > = 0 2 π b y Φ ( y ) e 2 d x = - ( λ - 4 a ) - 1 b 2 2 π 0 2 π ( x 2 e 2 2 + x 1 e 1 e 2 ) ( 2 x 1 x 2 e 3 - x 2 2 e 4 + x 1 2 e 4 ) d x + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 = - ( λ - 4 a ) - 1 b 2 2 π 0 2 π ( 2 x 1 2 x 2 e 1 e 2 e 3 - x 1 2 x 2 e 2 2 e 4 + x 2 3 e 2 2 e 4 ) d x + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equx_HTML.gif
Note that (5.4) hold true, we have
< G 2 ( y , Φ ( y ) ) , e 1 > = - ( λ - 4 a ) - 1 b 2 4 π x 1 3 - ( λ - 4 a ) - 1 b 2 4 π x 1 x 2 2 + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 , < G 2 ( y , Φ ( y ) ) , e 2 > = - ( λ - 4 a ) - 1 b 2 4 π x 2 3 - ( λ - 4 a ) - 1 b 2 4 π x 1 2 x 2 + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equy_HTML.gif
Since
0 2 π e 1 4 d x = 0 2 π e 2 4 d x = 3 4 π , 0 2 π e 1 2 e 2 2 d x = 1 4 π , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equz_HTML.gif
we have
< G 3 ( y , y , y ) , e 1 > = 0 2 π - d y 3 e 1 d x = - d 0 2 π x 1 3 e 1 4 + 3 x 1 x 2 2 e 1 2 e 2 2 d x = - 3 d 4 π x 1 3 - 3 d 4 π x 1 x 2 2 , < G 3 ( y , y , y ) , e 2 > = 0 2 π - d y 3 e 2 d x = - d 0 2 π ( 3 x 1 2 x 2 e 1 2 e 2 2 + x 2 3 e 2 4 ) d x = - 3 d 4 π x 2 3 - 3 d 4 π x 1 2 x 2 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equaa_HTML.gif
then we obtain the expression of < G(u), e j >, j = 1,2.
< G ( u ) , e 1 > = A x 1 3 + A x 1 x 2 2 + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 , < G ( u ) , e 2 > = A x 1 2 x 2 + A x 2 3 + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ23_HTML.gif
(5.8)

where A = - ( λ - 4 a ) - 1 b 2 2 π - 3 d 4 π http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_IEq20_HTML.gif.

Put (5.8) into (5.3), we have the approximation of reduction equation
d x 1 d t = ( λ - a ) x 1 + A x 1 3 + A x 1 x 2 2 + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 , d x 2 d t = ( λ - a ) x 2 + A x 1 2 x 2 + A x 2 3 + O λ - a 2 x 1 3 + x 2 3 + o x 1 3 + x 2 3 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equ24_HTML.gif
(5.9)
For the case of λ < a, it is obviously that u = 0 is locally asymptotically stable. For the case of λ = a, if 9ad > 2b2, which implies that A < 0, then u = 0 is also locally asymptotically stable. In particular, if b = 0, λa, by Poincaré inequality we have
1 2 d d t u H 2 = - a u x H 2 + λ u H 2 - d u H 4 ( λ - a ) u x H 2 - d u H 4 - d u H 4 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equab_HTML.gif

which implies that u = 0 is globally asymptotically stable. Assertion (1) of Theorem 3.2.1 be proved.

Since the following equality holds true
x 1 A x 1 3 + A x 1 x 2 2 + x 2 A x 1 2 x 2 + A x 2 3 = A x 1 2 + x 2 2 2 , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equac_HTML.gif

according to Theorem 4.1.2, we can conclude that if λ > a, the equation (1.1) bifurcates from u = 0 to an attractor Σ λ which is homeomorphic to S1. Assertion (2) and (4) of Theorem 3.2.1 are proved.

Step 4. In the last step, we shall show that the bifurcated attractor of (2.1) contains a singularity cycle.

By Krasnoselskii Theorem for potential operator, at least, L λ + G bifurcates from (u, λ) = (0,a) to a steady solutions (V λ , λ).

Since the solutions of (2.1) are translation invariant,
V λ ( x , t ) V λ ( x + θ , t ) , θ R , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equad_HTML.gif
the set
T = { V λ ( x + θ , t ) θ R } http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2012-41/MediaObjects/13661_2011_Article_159_Equae_HTML.gif

represents S1 in H1, which implies that assertion (3) of Theorem 3.2.1 is proved.

Declarations

Acknowledgements

The author was very grateful to the anonymous referees whose careful reading of the manuscript and valuable comments enhanced presentation of the manuscript. This research was supported by Scientific Research Foundation of Civil Aviation Flight University of China (J2011-30).

Authors’ Affiliations

(1)
College of Mathematics, Sichuan University
(2)
College of Computer Science, Civil Aviation Flight University of China

References

  1. Fisher RA: The wave of advance of advantageous genes. Ann Eugenics 1937, 7: 353-369.
  2. Kolmogorov A, Petrovskii I, Piskunov N: É tude de l' é quation de la diffusion avec croissance de la quantit é de lamatier é et son application á un probl é me biologique. Moscow Univ Bull Math 1937, 1: 1-25.
  3. Aronson DG, Weinberger HF: Nonlinear diffusion in population genetics, combustion, and nerve propagation. Partial Differential Equations and Related Topics. In Lecture Notes in Mathematics. Volume 446. Springer-Verlag, New York; 1975.
  4. Fife PC: Mathematical aspects of reacting and diffusing systems. In Lecture Notes in Biomathematics. Volume 28. Springer-Verlag, Berlin/New York; 1979.
  5. Murray JD: Mathematical Biology. Springer-Verlag, New York; 1989.View Article
  6. Harrison BK, Estabrook FB: Geometric approach to invariance groups and solution of partial differential systems. J Math Phys 1971, 12: 653-666. 10.1063/1.1665631MathSciNetView Article
  7. Ablowitz MJ, Zeppetella A: Explicit solutions of Fisher's equation for a special wave speed. Bull Math Biol 1979, 41(6):835-840.MathSciNetView Article
  8. Kawahaka T, Tanaka M: Interactions of traveling fronts: an exact solution of a nonlinear diffusion equation. Phys Lett A 1983, 97(8):311-314. 10.1016/0375-9601(83)90648-5MathSciNetView Article
  9. Ma WX, Fuchssteiner B: Explicit and exact solutions to a Kolmogorov-Petrovskii-Piskunov equation. Int J non-Liear Mech 1996, 31(3):329-338. 10.1016/0020-7462(95)00064-XMathSciNetView Article
  10. Clarkson PA, Mansfield EL: Symmetry reductions and exact solutions of a class of nonlinear heat equations. Phys D 1994, 70(3):250-288. 10.1016/0167-2789(94)90017-5MathSciNetView Article
  11. Kametaka Y: On the nonlinear diffusion equation of Kolmogorov-Petrovskii-Piskunov type. Osaka J Math 1976, 13: 11-66.MathSciNet
  12. Hamel F, Roques L: Fast propagation for KPP equations with slowly decaying initial conditions. J Diff Equ 2010, 249: 1726-1745. 10.1016/j.jde.2010.06.025MathSciNetView Article
  13. Moet HJK: A note on the asymptotic behavior of solutions of the KPP equation. SIAM J Math Anal 1979, 10(4):728-732. 10.1137/0510067MathSciNetView Article
  14. Rodrigo M, Mimura M: Annihilation dynamics in the KPP-Fisher equation. Eur J Appl Math 2002, 13: 195-204.MathSciNetView Article
  15. Ma T, Wang SH: Atttactor bifurcation theory and its applications to Rayleigh-B é nard convection. Commun. Pure Appl Anal 2003, 2(4):591-599.MathSciNetView Article
  16. Ma T, Wang SH: Bifurcation Theory and Applications. In Nonlinear Science Series A. Volume 53. World Scientific, Singapore; 2005.
  17. Ma T, Wang SH: Dynamic bifurcation of nonlinear evolution equations and applications. Chinese Annals Math 2005, 26(2):185-206. 10.1142/S0252959905000166View Article
  18. Park J: Bifurcation and stability of the generalized complex Ginzburg-Landau equation. Communications on Pure and Applied Analysis 2008, 7(5):1237-1253.MathSciNetView Article
  19. Zhang YD, Song LY, Axia W: Dynamical bifurcation for the Kuramoto-Sivashinsky equation. Nonlinear Analysis: Theory, Methods and Applications 2011, 74(4):1155-1163. 10.1016/j.na.2010.09.052MathSciNetView Article
  20. Temam R: Infinite-Dimensional Dynamical Systems in Mechanics and Physics. In Appl Math Sci. Volume 68. Springer, New York; 1997.
  21. Pazy A: Semigroups of Linear Operators and Applications to Partial Differential Equations. In Appl Math Sci. Volume 44. Springer, New York; 2006.
  22. Henry D: Geometric Theory of Semilinear Parobolic Equations. In Lectrue Notes in Matheatics. Volume 840. Springer-Verlag, New York; 1982.

Copyright

© Zhang; licensee Springer. 2012

This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://​creativecommons.​org/​licenses/​by/​2.​0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.